Adjustment for Growth : The African Experience - Tahari, Amor (Occasional Papers; Occasional Paper ;, 1996)
Over the past two decades, sub-Saharan Africa has lagged behind other regions in economic performance. The important overall indicators of performance, however, mask wide differences among countries. On the whole, countries that effectively implemented comprehensive adjustment and reform programs showed better results. Their experiences demonstrate that an expansion in private saving and investment is key to achieving gains in real per capita GDP. The four papers included in this publication provide a cross country analysis that assesses empirically the role of publlic policies in stimulating private saving and investment in the region in 1986-92 and describe the adjustment experiences of Ghana (1983-91), Senegal (1978-1993), and Uganda (1987-94).